Radiofrequency surgery of the tongue base in the treatment of snoring: a pilot study - Welt, Sandra; Maurer, Joachim T.; Hörmann, Karl; Stuck, Boris (Sleep and breathing, 2007)
In a previously published study, a significant reduction of snoring was reported after treatment with radiofrequency surgery of the tongue base in patients suffering from obstructive sleep apnea syndrome. The aim of this study was to investigate the efficacy of radiofrequency surgery of the tongue base in the treatment of primary snoring. Twenty patients suffering from primary snoring (AHI < 10/h, body mass index < 32 kg/m2) and an isolated hypertrophic tongue base at clinical examination were enrolled in this clinical trial. The patients underwent bipolar radiofrequency surgery of the tongue base under local anaesthesia. Pre- and post-operative body weight, daytime sleepiness (Epworth sleepiness scale) and snoring scores (visual analogue scales) were evaluated by the patients and their bed partners, respectively. Postoperative follow-up data was collected 6-8 weeks after treatment. A statistically significant reduction of the preoperative snoring levels from 7.5 ± 2.4 to 6.1 ± 2.8 was seen after treatment (p < 0.001). Body weight and daytime sleepiness remained unaffected. Only 3 out of 20 patients were satisfied with the result as defined by VAS < 3. Despite statistically significant reduction of the subjective snoring scores after radiofrequency of the tongue base, only minimal clinical improvement was achieved. Only 3 out of 20 patients were satisfied with the results. With regard to the clearly beneficial effect seen in patients with obstructive sleep apnea, this result indicates different pathophysiological principles in the generation of snoring.